PENERAPAN PERATURAN GUBERNUR BALI NOMOR 97 TAHUN 2018 TENTANG PEMBATASAN TIMBULAN SAMPAH PLASTIK SEKALI PAKAI DI KABUPATEN BULELENG - Saputra, Kadek Dodi Riawan; Hardianto, Hardianto; Pikahulan, Muis S. A. (IAIN Ambon, 2022)
Garbage is a big problem in any country and Indonesia is one of them. Due to the large amount of waste generated between 2019 and 2021, i.e. 92,397,017.56 tons, the reduction of waste in Indonesia is of great concern. Also, daily births varied and reached 253,142.51 tonnes. The amount is not small, which clearly shows that Indonesia's waste problem is an unsolved problem. The purpose of this study is to apply Bali Provincial Governor Decree No. 97 of 2018 on single-use plastic waste violence in Buleleng province and to encourage the government to reduce population dependence in Buleleng province to reduce overcoming plastic consumption. It was to investigate the initiative disposable plastic. The method used in this study is a descriptive empirical legal method. The research in this article shows that this is suboptimal. Penalties for offenders under Bali Governor Decree No. 97 of 2018 are subject to administrative sanctions only and therefore have no deterrent effect on offenders. Pursuant to Article 17(2) of Bali Governor's Decree No. 97 of 2018, the study found that the government's efforts to break the dependence of the people of Buleleng province on the use of single-use plastics are subject to guidance and supervision. was carried out by Through information, advice, technical assistance, training or support in waste prevention and government law enforcement practices, cleaner production and application of the 4R principles (reduce, reuse, recycle and replace) can be implemented.Keywords: Buleleng Regency, Governor of Bali Regulation Number 97 of 2018, Disposable Plastic, Garbage Generation